Interpretirte Welt - Schmidl, Stephan (Muzikološki zbornik, 2013)
Quite contrary to artist's biographies, music written under the influence of the Great War has been hardly ever considered as an explanatory source. To demonstrate its actual significance three aspects of World War One-music are to be illumined: musical modes of representing warring parties, ways of "translating" experiences of war into artificial sound and the use of music asa memory medium.
Keywords: glasba; glasbeno ponazarjanje; kulturni spomin; music; svetovna vojna 1914-1918